Functionalization of Reduced Graphene Oxide with β‐cyclodextrin Modified Palladium Nanoparticles for the Detection of Hydrazine in Environmental Water Samples. Issue 2 (15th September 2016) - Sakthinathan, Subramanian; Kubendhiran, Subbiramaniyan; Chen, Shen‐Ming; Sireesha, Pedaballi; Karuppiah, Chelladurai; Su, Chaochin
Abstract: A sensitive and selective hydrazine sensor was developed by β‐cyclodextrin modified palladium nanoparticles decorated reduced graphene oxide (PdNPs‐β‐CD/rGO) nanocomposite. The PdNPs‐β‐CD/rGO hybrid material was prepared by simple electrochemical method. The hydrophobic cavity of β‐CD ineracts with palladium nanoparticles by hydrophobic interaction and further it is uniformly assembled on the rGO surface through hydrogen bond formation, which is clearly confirmed by FT‐IR, FESEM and TEM. The high electrocatalytic activity of hydrazine oxidation was observed at −0.05 V (vs. Ag/AgCl) on PdNPs‐β‐CD/rGO modified electrode; due to the excellent stabilization, high catalytic activity and large surface area of the PdNPs‐β‐CD/rGO composite. The PdNPs‐β‐CD/rGO fabricated hydrazine sensor exhibited an excellent analytical performance, including high sensitivity (1.95 μA μM −1  cm −2 ), lower detection limit (28 nM) and a wide linear range (0.05 to 1600 μM). We also demonstrated that the PdNPs‐β‐CD/rGO nanocomposite modified electrode is a highly selective and sensitive sensor towards detection of hydrazine among the various interfering species. Hence, the proposed hydrazine sensor is able to determine hydrazine in different water samples. Abstract :